2004
DOI: 10.1007/s11664-004-0175-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel structure of woven continuous-carbon fiber composites with high electromagnetic shielding

Abstract: A novel structure employing the woven continuous-carbon fiber (CCF) epoxy composite with high electromagnetic (EM) shielding is presented experimentally and theoretically. The influences of weave type, number, and angle of overlapped plates upon the shielding effectiveness (SE) of the woven CCFepoxy composite are investigated. The minimum SE of the single, double, and triple-plain or balanced-twill woven CCF-composite plates was measured to be as high as 50 dB, 60 dB, and 70 dB, respectively. More than 100 dB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 16 publications
2
26
0
Order By: Relevance
“…Previous work done by the authors suggested several effective solutions [2,3]. One solution is to modify the nylon66/liquid crystal polymers (LCPs) composites by adding short or long electrically conductive discontinuous carbon fibers (CFs) to build a three-dimensional conductive network within the polymeric matrix.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous work done by the authors suggested several effective solutions [2,3]. One solution is to modify the nylon66/liquid crystal polymers (LCPs) composites by adding short or long electrically conductive discontinuous carbon fibers (CFs) to build a three-dimensional conductive network within the polymeric matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Although, many EM shielding methods [2][3][4][5][6][7][8][9][10] are available for electronic plastic packaging, not many methods are available for optical-electronic plastic packaging. Low cost, high EM shielding optical laser modules made with the modified thermosets using compression molding technology were reported [5,11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations